Model Kinerja Pegawai Melalui Kepuasan Kerja: Penempatan dan Lingkungan Kerja - Candana, Dori Mittra; putra, rio andhika; Purwasih, Ratih (Riset Sinergi Indonesia, 2023)
The results of the study show (a) there is a positive and significant effect between Placement on Satisfaction. Where the calculated t value is greater than t table (5.742 > 2.045) or the significant level is smaller than alpha (0.000 <0.05) (b) There is a positive and significant influence between the work environment on job satisfaction in. Where the calculated t value is greater than t table (4.295 > 2.045) or a significantly smaller level than alpha (0.000 <0.05) (c) There is a positive and significant effect between Placement on Performance. . Where t count is greater than t table (5.728 > 2.045) or a significant level equal to alpha (0.000 <0.05) (d) There is a positive and significant influence between the Work Environment on Employee Performance. Where the calculated t value is greater than t table (2.392 > 2.045) or the significant level is smaller than alpha (0.022 <0.05) (e) There is a positive and significant influence between Job Satisfaction on Employee Performance. Where t-count is greater than t-table (3.331 > 2.045) or significantly lower than alpha (0.002 <0.05) (f) Job satisfaction can mediate Placement on Employee Performance. Where the indirect effect is greater than the direct effect (0.772 > 0.577) (g) Job satisfaction is able to mediate the work environment on employee performance. Where the indirect effect is greater than the direct effect (0.37 > 0.224).Keywords : Employee Performance, Job Satisfaction, Placement and Work Environment